Analysis of Office Supplies Control Management in Setdaprovsu Organizational Bureau - Lidiya Uzmasyah; Yenni Samri Julianty Nasution (Penerbit Jurnal Indonesia, 2022)
Control of office equipment is the activity of providing all goods/services for the purposes of executing the task. The process of providing office facilities through an assessment carried out by government agencies. Office equipment used must be adjusted to the needs of the office so that it is not excessive which results in redundancy. Office facilities at each company will be different in type, depending on the type of business and the size of the company. In the Organizational Bureau, many need HVS paper, printer ink, envelopes, stamps and so on. The purpose of this study is to determine the plan for controlling office equipment at the Regional Secretariat of the Regional Secretariat of the Organization, the problem is how the Organizational Bureau regulates the control of the office equipment. It is hoped that this research has theoretical and practical benefits that will assist in controlling office supplies at the Regional Secretariat of the Provincial Secretariat Organization Bureau. The method used is a descriptive qualitative approach. The subject of this research by way of interviews. The results of this study indicate that implementing the office equipment control management function can provide benefits for managing office supplies inventory at the Regional Secretariat Organization Bureau.